Zur Problematik von Zusammenhang und Disparität zwischen Orgelrepertoire, Improvisation und Ensemble-Intonation - Ortgies, Ibo (Muzikološki zbornik, 2011)
The relation of organ temperament to almost all areas of musical practice in Northern and Central Germany in the seventeenth and eighteenth centuries makes it an indispensable factor in historical performance practice. The issue of organ temperament has either been viewed as part of the general historical development of temperament theory, or has been viewed from the alleged connection with compositions that were considered to be 'organ repertoire', but this has often been seen from a later liturgical or organ concert practice. The relationship between ensemble intonation and organ temperament has been underestimated in modern times and has therefore hardly ever been considered. It seems that the present attitudes and customs within performance practice have in part been obstacles to understanding the relationships among organ playing, compositions, organ temperament and performance practice in Northern and Central Germany in the seventeenth and eighteenth centuries. This article tries to remove some of those obstacles.
Keywords: ansambelska igra; ensemble playing; historical performance practice; improvisation; improvizacija; organ repertoire; orgelski repertoar; temperament; uglasitev; zgodovinska izvajalska praksa